Feasibility assessment of solution mining and gas storage in salt caverns: a case study of the Sanshui salt mine - Yi, Weikai; Li, Qihang; Zhao, Xiangyang; Liu, Wei; Du, Jinwu (Frontiers in Energy Research, 2023)
Sanshui salt mine is the sole location in Guangdong Province of South China with the potential to construct a salt cavern gas storage (SCGS) facility. To demonstrate the feasibility and calculate the gas storage capacity in this specific mining area, two representative salt caverns within this salt mine were simulated by using a self‒ developed cavern‒building simulation program, enabling us to accurately determine their respective volumes and shapes. Herein the findings indicate that the combined caverns possess a total mining space volume of 1,157,000 m3, with the brine space accounting for merely 291,800 m3 (representing 25.22% of the overall mining space), as well as an extensive sedimentary volume of 865,200 m3 is observed (constituting approximately 74.78% of the total mining capacity). Fortunately, this study has revealed that the sediments exhibit a porosity exceeding 40% and process favorable permeability, consequently, countermeasures have been proposed to enhance gas storage capacity within the pore space of these caverns, and we also utilized FLAC3D software for numerical simulation calculations to compare the stability of the cavern under different conditions of sediment pore utilization by calculating the volume loss rate, cavern wall displacement deformation, and plastic zone distribution. Moreover, the proposed method is anticipated to double the caverns’ working gas volume, increasing it from 40 million m3 to nearly 80 million m3. On the other hand, the long‒term stability of caverns is numerically assessed under different pore space utilization rates of the sediments. The results also indicate that the caverns’ volume shrinkage, plastic zones and surrounding rock displacement remain within allowable limits during 30 years of gas storage operation. The primary problem in the subsequent phase lies in effectively achieving gas injection and brine removal from the pore space of sediments, while devising a methodology to extend this method to other salt caverns within similar salt mine areas. Thus, this study provides theoretical and technical guidance for the establishment of gas storage in existing salt caverns in Sanshui salt mine, and in salt mines worldwide that share similar geological conditions.